Pemeringkatan Kinerja Keuangan Perbankan di Indonesia Menggunakan Metode TOPSIS Berbasis Entropi - Dwiyanto, Riski; Rasyid, Rosyeni (Jurnal Manajemen Bisnis dan Keuangan, 2025)
Accurate and objective assessment of banking financial performance is crucial in promoting transparency and accountability within the financial sector. Traditionally, bank performance evaluations have focused on conventional financial indicators that do not fully capture actual cash dynamics. This study aims to rank the financial performance of Indonesian banks based on cash flow ratios using the entropy-based TOPSIS method. Eight cash flow ratios covering liquidity, operational efficiency, financial structure, and profitability aspects are employed as the evaluation criteria. The entropy method is applied to determine the objective weights of each criterion based on data variability, while TOPSIS is used to rank the banks according to their relative closeness to the ideal solution. The findings reveal that the ratio weights vary from year to year, reflecting the dynamic nature of financial information across periods. These changes significantly affect bank rankings, indicating that cash performance tends to fluctuate. The results confirm that the entropy-based TOPSIS method is effective in providing an objective and adaptive ranking system that reflects actual financial conditions. Honesty and the protection of consumer rights contribute to long-term relationships between businesses and customers. This research also aims to explore the application of Islamic business ethics in marketing, focusing on halal products, fair pricing, and ethical promotion. Using a qualitative literature review approach, the study analyzes how integrating Sharia principles into marketing practices can enhance market relevance, build consumer trust, and foster sustainable business growth in a diverse global context. The findings offer strategic insights for marketers seeking to engage ethically and effectively with predominantly Muslim markets.